Institutional ownership and firm performance: Evidence from an emerging economy - Syeda Humayra Abedin; Humaira Haque; Tanjina Shahjahan; Md. Nurul Kabir (Journal of Risk and Financial Management, 2022)
Using the Ordinary Least Square (OLS) estimation technique based on a sample of 180 listed firms from 2008 to 2018, this study investigates the impact of institutional ownership on firm performance in the Bangladeshi setting. Consistent with the "active monitoring" view, the results indicate that both domestic and foreign institutional investors have a positive effect on firm performance measured by Tobin's Q and Return on Asset (ROA). In addition, this study explores whether the other corporate governance attributes-board size and board independence-operate as mediators between institutional ownership and firm performance. Our findings indicate that both board size and board independence have a significant positive impact on the relationship between institutional ownership and firm performance.
Keywords: G01; G32; G33; G34; G38; 650; foreign ownership; ROA; board independence; board ownership; domestic ownership; institutional ownership; Tobin's Q